Neper2CAE and PyCiGen: scripts to generate polycrystals and interface elements in Abaqus - Grilli, N; Tarleton, E; Cocks, ACF (Elsevier, 2021)
Two codes have been developed: one allows columnar polycrystal geometries generated by software such as Neper or DREAM3D to be imported into the Complete Abaqus Environment for further geometric manipulation and meshing with arbitrary element types; the other code generates zero thickness, four noded interface elements at the boundaries between the crystals. Together these allow intergranular fracture simulations to be performed easily in Abaqus. This approach can automatically create different grain structures and allows the mechanical properties of metals and other crystalline materials to be simulated. This is important as it enables the sample to sample variability of fracture and mechanical properties that is observed in experiments to be reproduced. These scripts extend the simulation capabilities of the finite element solver Abaqus.